The application of gravity equation while accessing the environment of Pakistan-ASEAN technological trade flows - Muhammad Saqib Irshad; Zhang Jian Wu; Qi Xin; Jahangir Khan (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2021)
International trade, an important economic activity, has affected the human environment in varying degrees since its beginning. This research will carry out calculations and analyses on Pakistan-ASEAN bilateral and technological trade flows at a disaggregated level over 1995-2018. The current study found that medium-tech, high-tech, and low-tech trade flows, enhance economic growth in Pakistan and ASEAN, negatively impacting geographical distance by all technological trade flows. Similarly, the proportional element endowment confirms the Hecksher-Ohlin hypothesis. Yet, the perspective argues that countries with high production levels can exchange faster than their countries with lower output levels. Due to the variety in consumers’ taste, increased similarity yields increased technological trade volumes, highest values received by medium-tech trade flow, and total bilateral trade flow. Depreciation in exchange rates showing a positive sign for total bilateral trade, low-tech trade, and high-tech trade, whereas unenthusiastic in the case of medium-tech trade flow between Pakistan-ASEAN nations. Free trade agreement and WTO membership will also foster trade activities in conscientious and economic association in ecumenical. Pakistan trade patterns are different from ASEAN trade patterns, which increased the opportunity to enhance business activities.